Building on indigenous knowledge to strengthen the capacity of smallholder farming communities to adapt to climate change and variability in southern Africa. (1st January 2016) - Mapfumo, Paul; Mtambanengwe, Florence; Chikowo, Regis
Abstract : A study was conducted in Makoni and Hwedza smallholder farming areas in eastern Zimbabwe to investigate local perceptions of the impacts of climate change and variability, and how indigenous knowledge may enable farmers to construct appropriate responses to these impacts and make key agricultural decisions. The study revealed evidence of increased climate variability and heightening vulnerability in farming systems. Rainfall seasons have shortened by up to four weeks, impacting on food sources and ecosystem services, and increasing pressure on women and children as traditional roles change. Communities depended primarily on indigenous knowledge and local biological and geographical indicators of seasonal forecasts in making major strategic, tactical and operational decisions on crop production, including management of food stocks and social safety nets. In providing climate and technical production information, researchers and development practitioners will therefore need to fit in with farmers' local decision-making frameworks. However, it should be recognized that some of the indicators (e.g. biological) on which this indigenous knowledge is traditionally based are also adversely affected by increased climate variability, placing limits on its scope as a basis for decision-making. Despite this, efforts to build the adaptive capacity of these farming communities should still consider the current indigenous knowledge base as an entry point.